2019
DOI: 10.3390/dj7020060
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia, Oral Health and Antioxidant Salivary System: A Clinical Study on Adult Female Subjects

Abstract: The aim of this study was to compare the oral health status and salivary antioxidant system between patients diagnosed with anorexia nervosa (AN) and healthy controls. A total of 25 female AN patients and 25 matched healthy controls were enrolled. Clinical parameters and saliva samples were collected for each patient. Two questionnaires to investigate oral health and hygiene were administered. Superoxide Dismutase (SOD) activity and High Reactive Oxygen Species (hROS) were evaluated. Salivary concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…In animal models, increased epithelial tissue SOD activity relative to the control group was found after anticonvulsant drug treatment (Wu et al, 2018), a kind of drug used by this group. Nutritional alterations resulted in chewing problems and dysphagia in MC groups; they may also be involved in the greater SOD activity observed in saliva, similarly to what has already been described with nutritional problems resulting from anorexia (Mascitti et al, 2019). When SOD was expressed in relation of total protein (U/mg) these increased of activity is not observed, because protein total is higher in saliva of the MC group than NC group.…”
Section: Discussionsupporting
confidence: 65%
“…In animal models, increased epithelial tissue SOD activity relative to the control group was found after anticonvulsant drug treatment (Wu et al, 2018), a kind of drug used by this group. Nutritional alterations resulted in chewing problems and dysphagia in MC groups; they may also be involved in the greater SOD activity observed in saliva, similarly to what has already been described with nutritional problems resulting from anorexia (Mascitti et al, 2019). When SOD was expressed in relation of total protein (U/mg) these increased of activity is not observed, because protein total is higher in saliva of the MC group than NC group.…”
Section: Discussionsupporting
confidence: 65%
“…This enzyme is capable of increasing in response to different inflammatory diseases such as pulpitis and periodontitis. SOD is able to protect the oral cavity against the effects of ROS, which could be considered a partial compensatory response when there is oxidative stress in the cavity, and SOD represents the first defense in the antioxidant tissues [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Panico et al (2018) [60] and Lesar et al (2022) [61] observed oral lesions in up to 94% of patients. Their locations can be on the lips, which are dry in as many as 76.2% [62], 93.2% [52], or 69% [28] of subjects. In addition, exfoliative cheilitis, angular cheilitis, and labial erythema are very frequently diagnosed [1,52,53,60,61,63].…”
Section: Oral Mucosal Healthmentioning
confidence: 99%